Suicide in doctors. A psychological autopsy study. - Hawton, K; Malmberg, A; Simkin, S (2004)
OBJECTIVES: Doctors are at higher risk of suicide than many other occupational groups. This study was conducted to investigate factors associated with suicide in doctors. METHOD: Psychological autopsy study of 38 working doctors who died by suicide in England and Wales between January 1991 and December 1993. RESULTS: Psychiatric illness was present in 25 of the doctors. Depressive illness and drug or alcohol abuse were the most common diagnoses. Twenty-five doctors had significant problems related to work, 14 had relationship problems and 10 had financial problems. Multiple and interrelated problems were often present. The most common method of suicide was self-poisoning, often with drugs taken from work. CONCLUSION: Prevention of suicide in doctors requires a range of strategies, including improved management of psychiatric disorder, measures to reduce occupational stress and restriction of access to means of suicide when doctors are depressed.